Pengaruh model pembelajaran kooperatif tipe student team achievement division (STAD) berbantuan geogebra terhadap kemampuan komunikasi matematika siswa - Arifin, Monica Chinlie (Prosiding Seminar Nasional Matematika dan Pendidikan Matematika, 2020)
The purpose of this study was to determine the effect of STAD type cooperative learning models assisted by Geogebra to students’ mathematical communication skills. This study was a quasi-experimental study with a sample of 3 classes that were randomly assigned to groups. Research data were collected using essay tests. Data were analyzed using analysis of covariances techniques. The results of the study concluded that there was a significant influence on the application of the STAD (two variable linier equation system) cooperative learning model assisted by Geogebra to students ’mathematical communication skills on SPLDV material in class X. The results of the analysis also indicated that the students’ mathematical communication skills were taught with the STAD type cooperative learning model assisted by Geogebra is significantly higher than the mathematics communication skills of students who are taught STAD type cooperative learning models without the media or who are taught with direct learning models.